Microbiome Status of Cider-Apples, from Orchard to Processing, with a Special Focus on Penicillium expansum Occurrence and Patulin Contamination - Reem Al Riachy; Caroline Strub; Noël Durand; Benjamin Guibert; Hugues Guichard; Florentin Constancias; Vincent Chochois; Félicie Lopez-Lauri; Angélique Fontana; Sabine Schorr-Galindo (Journal of Fungi, 2021)
Patulin is a secondary metabolite produced primarily by the fungus Penicillium expansum, responsible for the blue mold disease on apples. It is found in apple products including apple cider when apple juice is added after fermentation. In the present study, two hundred and twenty-five cider-apples of the variety “Bedan”, cultivated in Brittany in France, were sampled from the orchard during harvesting until the storage step, right before processing. The patulin analysis on these samples reported a low contamination at the orchard and a significantly higher-level of contamination in the cider-apples starting from the transporting bin. The percentage of positive samples increased from 6% to 47% after 12 h in the harvesting bin before transporting and reached 95% after 24 h of transporting, decreasing then to 69% at the end of the storage. Penicillium expansum was quantified on the surface of apples using real-time PCR and was observed to be mostly consistent between the harvest and post-harvest steps. It was detected on average, on the surface of 85% of all sampled apples with a mean value around 2.35 × 106Penicillium expansum DNA/g of apple. Moreover, the changes in the fungal and bacterial epiphytic microbiota in the different steps were studied using a metabarcoding approach. The alpha and beta diversity analysis revealed the presence of unique and more diverse bacterial and fungal communities on the surface of apples picked from the orchard compared to the rest of the sampling steps. Potential indigenous biological control agents were identified on the surface of sampled apples. Future perspective includes developing actions of prevention and control of the contamination by Penicillium expansum during the harvest and along the various critical post-harvest stages before transformation in a sustainable development concern.